Use of Ceftolozane/Tazobactam in a Case of Septic Shock by Puerperal Sepsis - Mario Pezzi; Anna Maria Scozzafava; Anna Maria Giglio; Renata Vozzo; Patrizia Dina Casella; Simona Paola Tiburzi; Lucio Cosco; Mario Verre (Hindawi Limited, 2019)
Multiresistant bacteria infections cause widespread morbidity and mortality and lead to an increase in expenses for hospital stays and complications. We describe the case of a 27-year-old patient with puerperal sepsis after cesarean section due to Escherichia coli complicated by multiresistant Klebsiella ESBL-producing superinfection with septic shock and multiple organ dysfunction syndrome, successfully treated with ceftolozane/tazobactam.